The Big Lebowski [videorecording (DVD)] - Coen, Ethan; Coen, Ethan; Coen, Joel; Coen, Joel; Bridges, Jeff, 1949-; Goodman, John, 1952-; Moore, Julianne; Buscemi, Steve, 1957-; Stormare, Peter; Huddleston, David, 1930-2016; Elliott, Sam, 1944- (Focus Features : Universal Studios Home Entertainment, 2005)
A lazy, unemployed Southern Californian stoner who loves bowling gets mistaken for a millionaire with the same name. He's beaten up by men looking for money from the rich man's wife and gets drawn into the kidnapping of the millionaire's wife.